Caribbean stones and the creation of early-modern worlds. (2nd January 2018) - Gómez, Pablo F.
ABSTRACT: This article considers the role that objects which anthropologists and historians have labeled ritual stones perform in the theorization of early modern worlds' materiality. These stones function primordially as locators of epistemic and ontological difference. They define the categories through which historians engage early-modern things that are similar to these metonymically construed objects only in naturalistic terms. Histories that engage with "non-western" technologies stem in many cases from a benevolent impulse of paternalistic inclusivity. Such projects, however, depend ostensibly on the identification of certain types of things as being part of a world that is not, really, ours. The history of the criollo/creole things of the early modern Caribbean invites us to think of objects like seventeenth-century Caribbean stones, not as elements belonging in realms of incommensurable alterity, but instead as part of a shared history, one that belongs intrinsically together with the history of "the moderns" and their things.